TOPONYMS AND NAMES OF HISTORICAL PERSONS IN THE PRESENT-DAY URBANONYMS OF LATGALE REGION - Matisovs, Ivars (Via Latgalica, 2013)
Entire set of names presented in the urban area is considered to be urbanonyms – these are the names of address objects (streets, squares, etc.) and the names of other urban objects (parks, hillforts, markets, cemeteries, etc.), as well as the names of separate urban housing estates – both offi cially approved by the authorities and arbitrarily nominated by the population. Urbanonyms are featuring originality of geographical location and particularity of topographical environment of the town or the city, displaying cultural and historical realities, and opening ideological statements of the epoch. In the towns and cities of Latgale during the initial period of formation of the streets, naming thereof has been closely linked to the immediate perception of urban environment and has been taking place spontaneously, by the system of urbanonyms representing territorial features of terrain, type of land use, landscapes and hydrographic network. Urbanonyms in the same way are describing the elements and the most important objects of the urban social and economic infrastructure, for that reason they very often appear also in street names of the towns and cities. The most widely used urbanonym in Latgale is represented by Skolas (School) street, which is found in 13 towns and cities of Latgale region, as the most popular urbanonyms also Baznīcas (Church) (in 10 towns and cities), Parka (Park) and Tirgus (Market) streets (in 9 towns and cities), Dzirnavu (Mill) and Stacijas (Station) streets (in 8 towns and cities) have to be mentioned. Over the 20th century, ideological strata of different powers have had an increasingly high impact on the urbanonyms, for example, more and more frequent naming the streets after notable historic persons or events, in the same way urbanonyms have had to promote emergence of connotations beneficial to the existing power. It is likewise understandable, since urbanonyms are affecting views with regard to the surrounding world of urban residents already since their childhood. It is established that urbanonyms "are the language segment, where ideology of each power is expressed in the most pronounced way” (Balode 2008) and "urbanonyms are national symbols – the same as flag and anthem” (Питкевич 2007). The research is aimed to provide extended characteristics of the Latgale urbanonyms, encompassing all the 14 towns and cities of the Latgale planning region (Balvi, Dagda, Daugavpils, Ilūkste, Kārsava, Krāslava, Līvāni, Ludza, Preiļi, Rēzekne, Subate, Viļaka, Viļāni, Zilupe), as well as Varakļāni belonging to the cultural and historical region of Latgale. Topicalities of the studies of urbanonyms and issues related to their definition and classification are also being dealt with. In-depth analysis is being provided for the use of various categories of place-names or toponyms in contemporaneous urbanonyms of Latgale, trying to reveal also geographical regularities of their selection. Concurrently also various aspects of perpetuation of the memory of historical persons in the street names are discussed – both those reflecting cultural and historical realities of the region and those imposed by ideological settings of different powers. Toponyms are of major importance in street names of the towns and the cities of Latgale – their totality amounts to 132 units, but their frequency of names – 208. Toponyms constitute 17.1 % of total number of the object address names. 81 toponyms or 63.3 % from their total numbers are related to Latgale region, but according to their frequency major proportion is made by names of other Latvian towns and cities. The most frequent toponyms among urbanonyms in Latgale include: Latgale (9 nominations), Rīga (8 nominations), Rēzekne (7 nominations), Daugavpils, Ludza, Jelgava (6 nominations), Vidzeme, Liepāja (5 nominations). In the urbanonyms of Latgale anthroponyms are used significantly less than toponyms, for example, names of historical persons in Latgale are represented only by 84 denominations that make up 6.9 % of their totality. Notwithstanding the fact that after the Republic of Latvia regained its national independence, in many places change of the urbanonyms ideologically unacceptable for the new power has been taking place, the urbanonyms of Latgale still have maintained a comparatively large number of imprints of Soviet ideology - in particular it is typical for Daugavpils as the largest city in the region. Perpetuation into urbanonyms of the names of famous native residents once having lived in particular town or city should be particularly encouraged, thus maintaining live memory of the urban cultural and historical heritage, and also inculcating the feelings of patriotism into townspeople. Urbanonyms with immediate link to the geographical environment, and cultural and historical realities of the territory are providing assistance in highlighting particularity of the region, strengthening historical memory of the socium and promoting a sense of belonging to one’s own place of residence. The article has been developed within the framework of the ESF project No.2009/0227/1DP/1.1.1.2.0/09/APAI/VIAA/071 “Linguo-culturological and Socio- economic Aspects of Territorial Identity in the Development of the Region of Latgale”.